2019
DOI: 10.1590/1517-869220192503188171
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Physical Activities Performed by Adolescents From Curitiba, Brazil

Abstract: Introduction Various studies have been developed and published in relation to the recommendations for physical activity and associated factors. However, there is a lack of studies that detail the places where physical activity is practiced, as well as its frequency, duration and volume. Objective To describe the places, types, frequency, duration and volume of physical activities performed by adolescents in Curitiba, Brazil. Methods A cross-sectional study conducted in 2013-2014, through a household survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
(44 reference statements)
0
5
0
3
Order By: Relevance
“…Thus, our study targeted adolescents aged from 15 to 17 years. Active transportation to school (ATS) is an effective way of incorporating PA into daily activities and increasing adolescents’ overall PA levels 1 , 2 – especially during transition from late adolescence to young adulthood, a critical period for decreasing PA levels 16 18 . Mandic et al 19 , point that adolescents’ decision in adopting ATS may be influenced by several factors of personal, social, or environmental nature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, our study targeted adolescents aged from 15 to 17 years. Active transportation to school (ATS) is an effective way of incorporating PA into daily activities and increasing adolescents’ overall PA levels 1 , 2 – especially during transition from late adolescence to young adulthood, a critical period for decreasing PA levels 16 18 . Mandic et al 19 , point that adolescents’ decision in adopting ATS may be influenced by several factors of personal, social, or environmental nature.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies 1 4 also found a higher prevalence of active transportation among girls, but they are not unanimous, so these results should be interpreted with caution. Girls’ PA levels are lower than their peers in the context of leisure 18 , so transportation may be a way to increase girls’ PA. However, further research is required to investigate the prevalence of ATS considering gender.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…O presente estudo também apresenta pontos positivos como a descrição das frequências dos tipos de atividade entre os praticantes de atividade física em todo território nacional. Normalmente, estudos com praticantes de atividade física limitam-se a amostra locais 28,29 . A utilização de dados da PNS, que apresenta representatividade nacional, é um importante passo para compreender as preferências regionais por alguns tipos de atividade no país.…”
Section: Discussionunclassified